Disparities in Liver Cancer Surveillance Among People With Disabilities: A National Database Study in Korea. Issue 5 (May 2021) - Seo, Jae Youn; Shin, Dong Wook; Yu, Su Jong; Jung, Jin Hyung; Han, Kyungdo; Cho, In Young; Kim, So Young; Choi, Kui Son; Park, Jong Heon; Park, Jong Hyock; Kawachi, Ichiro
Abstract : Goal: The goal of this study was to determine disparities in liver cancer surveillance among people with disabilities is the goal of this study. Background: Using the linked administrative database in Korea, we sought to investigate (1) whether there are disparities in liver cancer surveillance according to degree and type of disability and (2) temporal trends in liver cancer surveillance among people with disabilities. Materials and Methods: We linked national disability registration data with national cancer surveillance data. We analyzed age-standardized participation rates for each year during the 2006-2015 period according to presence, type, and severity of the disability. We also examined factors associated with liver cancer surveillance by multivariate logistic regression using the most current data (2014-2015). Results: The age-adjusted and sex-adjusted surveillance rate for liver cancer in people with disabilities increased from 25.7% in 2006 to 49.6% in 2015; however, during the same period, surveillance rate among people without disabilities increased from 24.9% to 54.5%. As a result, disparities in surveillance for liver cancer increased over time. The surveillance participation rate among people with disabilities was 12% lower than among people without disabilities. Surveillance rates were markedly lower among people with severe disabilities [adjusted odds ratio (aOR)=0.71] and people with renal disease (aOR=0.43), brain injuries (aOR=0.60), ostomy problems (aOR=0.60), and intellectual disabilities (aOR=0.69). Conclusions: Despite the availability of a national liver cancer surveillance program, a marked disparity was found in liver cancer surveillance participation, especially among people with severe disabilities, renal disease, or brain-related or mental disabilities. Abstract : Supplemental Digital Content is available in the text.